Comparative analysis of Salmonella enterica serovar Enteritidis mutants with a vaccine potential - Karasova, D; Sebkova, A; Vrbas, V; Havlickova, H; Sisak, F; Rychlik, I (Vaccine, 2009)
If any new live Salmonella vaccine is introduced in the future, it is quite probable that detailed characterisation of its attenuation will be required. In this study we therefore compared 34 isogenic mutants of S. Enteritidis in aroA, aroD, galE, ssrA, sseA, phoP, rpoS, ompR, htrA, clpP, lon, rfaL, rfaG, rfaC, hfq, sodCI, hilA, sipA, avrA, sopB, sopA, sopE, sifA, shdA, fliC, fur, relA, spoT, rel-spoT, misL, rmbA, STM4258, STM4259 and spvBC genes for their resistance to stresses likely to be expected in the host and for their virulence and immunogenicity in Balb/C mice. We found that the cold and bile resistances essentially did not correlate with the resistances to other stress factors. Resistance to acid pH, heat, polymyxin and serum correlated with each other and also with the attenuation. When the residual virulence and immunogenicity were both considered, mutants in htrA, ompR, aroA, aroD and lon performed the best in mice. Furthermore, when a detailed comparison of polymyxin and serum sensitive mutants was performed, the serum sensitive mutants were more immunogenic.
Keywords: polymyxiny; Virulence; Animals; Female; salmonelové vakcíny; ženské pohlaví; delece genu; Salmonella Vaccines; bakteriální geny; Reproducibility of Results; Mice; salmonelová infekce u zvířat; Polymyxins; Mice, Inbred BALB C; myši; Salmonella enteritidis; virulence; reprodukovatelnost výsledků; Gene Deletion; myši inbrední BALB C; Vaccines, Attenuated; Salmonella Infections, Animal; Genes, Bacterial; zvířata; atenuované vakcíny